Neuronal congruency effects in macaque prefrontal cortex - Tao Yao; Wim Vanduffel (Nature Communications, 2022)
Stimulus-induced conflicts impair behavior in conflict tasks resulting in a phenomenon known as the behavioral congruency effect. Here, the authors investigate the neural underpinnings of this phenomenon and report a neuronal congruency effect in macaque prefrontal cortex to explain this impairment.